2022
DOI: 10.3390/ma15020507
|View full text |Cite
|
Sign up to set email alerts
|

Failure Criteria and Constitutive Relationship of Lightweight Aggregate Concrete under Triaxial Compression

Abstract: This paper investigates the compression behavior and failure criteria of lightweight aggregate concrete (LAC) under triaxial loading. A total of 156 specimens were tested for three parameters: concrete strength, lateral confining pressure and aggregate immersion time, and their effects on the failure mode of LAC and the triaxial stress-strain relationship of LAC is studied. The research indicated that, as the lateral constraint of the specimen increases, the failure patterns change from vertical splitting fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Over the years, many researchers have conducted extensive experimental studies and theoretical analyses of concrete strength theory. [40][41][42] At present, there are few reports on the failure criterion of GFRAC under complex stress state. Consequently, we discuss the failure criteria of GFRAC under three-dimensional stress state in this paper.…”
Section: Gfrac Failure Criterion Under Triaxial Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, many researchers have conducted extensive experimental studies and theoretical analyses of concrete strength theory. [40][41][42] At present, there are few reports on the failure criterion of GFRAC under complex stress state. Consequently, we discuss the failure criteria of GFRAC under three-dimensional stress state in this paper.…”
Section: Gfrac Failure Criterion Under Triaxial Compressionmentioning
confidence: 99%
“…The failure criterion is a mathematical function that describes the failure envelope of the concrete and serves as a condition to determine whether the concrete has reached the failure state or ultimate strength. Over the years, many researchers have conducted extensive experimental studies and theoretical analyses of concrete strength theory 40–42 . At present, there are few reports on the failure criterion of GFRAC under complex stress state.…”
Section: Gfrac Failure Criterion Under Triaxial Compressionmentioning
confidence: 99%
“…Failure cracks will propagate along the shells of the aggregates, resembling those found in normal weight aggregates. These aggregates can exhibit a distinct failure process, as cracks may propagate directly through them (13) . This research highlights the significance of adding basalt fibre as secondary reinforcement in reducing the inherent drawbacks of sintered flyash LWAC like cracking behavior and failure mode.…”
Section: Introductionmentioning
confidence: 99%
“…So far, scholars from various countries have achieved more fruitful results on the mechanical properties of coral concrete [9][10][11]. In 1974, Howdyshell P A [12], a U.S. Army Construction Engineering Laboratory scholar, published a research study on coral concrete and concluded that "it is feasible to formulate concrete using coarse coral aggregates, but the chloride salt content of coral aggregates should be controlled".…”
Section: Introductionmentioning
confidence: 99%